Ada Lovelace: The First Computer Programmer and Why She Is Important to Nursing Informatics. - Carter-Templeton, Heather; Newton, Sarah E.; Maas, Alexander N. (CIN: Computers, Informatics, Nursing, 2025)
Computers are ubiquitous to nursing and nursing practice, often in the form of electronic health records. Most nurses do not know the history of computers, how they were developed, or who the computing pioneers were that enabled the discipline of nursing to use this technology in its practices. Computers were first envisioned in the early 19th century, and one of the most influential computer programming visionaries was Ada Lovelace. It is important for the discipline of nursing to know Ada Lovelace, not only who she was, but also how her pioneering work influenced the history of computer technology. This article highlights the life of Ada Lovelace, her contributions to computer programming, and how her work paved the way for the use of computers in nursing and, ultimately, nursing informatics as a nursing specialty.